How to understand the underlying structures of X(4140), X(4274), X(4500) and X(4700) - Xiao-Hai Liu (Physics Letters B, 2017)
We investigate the possible rescattering effects which may contribute to the process B+→J/ψϕK+. It is shown that the ψ′ϕ rescattering via the ψ′K1 loop can simulate the structure of X(4700). The cusp effect due to the Ds⁎+Ds− rescattering may possibly simulate the X(4140) structure, but it depends on the cusp model parameters. If the quantum numbers of X(4274) (X(4500)) are 1++ (0++), it is hard to ascribe the observation of X(4274) and X(4500) to the P-wave threshold rescattering effects, which implies that X(4274) and X(4500) could be genuine resonances. We also suggest that X(4274) may be the conventional orbitally excited state χc1(3P).